The Tribological and Mechanical Properties of Pdcpd/Pew Composites Prepared by Reaction Injection Moulding. Issue 1 (January 2015) - Wang, Liping; Pan, Bingli; Du, Jinping; Cheng, Yumei; Liu, Jichun; Du, Sanming; Shangguan, Bao; Zhang, Yongzhen
In order to improve mechanical performance and wear resistance of polydicyclopentadiene (PDCPD) by convenient methods and technologies, novel PDCPD/polyethylene wax (PEW) composites were prepared by in-situ polymerization in a simulated reaction injection moulding. Studies on the mechanical and tribological properties of the composites were carried out. The bending strength and hardness of PDCPD/PEW composites significantly improved compared with neat PDCPD. The incorporation of PEW in PDCPD greatly enhanced the wear resistance and reduced the friction coefficients. The wear mass loss and friction coefficients for PDCPD/ PEW composites decreased continuously in the range of our experiments. The SEM micrographs of the worn surface showed the friction and wear mechanism of PDCPD.